Ginsenoside Rc, as an FXR activator, alleviates acetaminophen-induced hepatotoxicity via relieving inflammation and oxidative stress - Zhong, Yadi; Chen, Yingjian; Pan, Zhisen; Tang, Kaijia; Zhong, Guangcheng; Guo, Jingyi; Cui, Tianqi; Li, Tianyao; Duan, Siwei; Yang, Xiaoying; Gao, Yong; Wang, Qi; et al. (Frontiers in Pharmacology, 2022)
Acetaminophen (APAP) intake leads to excessive NAPQI deposition, stimulating served inflammatory and oxidative stress, and causing fatal liver injury. However, the detailed molecular mechanism and effective therapeutic approaches remain insufficient. In this study, we made a new discovery that the treatment with ginsenoside Rc can remove the inflammatory response caused by APAP and oxidative stress in mouse primary hepatocytes (MPHs), along with the corresponding change of related genes. Besides, Ginsenoside Rc effectively alleviates APAP-induced cellular apoptosis and NAPQI accumulation in MPHs. In vivo, Ginsenoside Rc administration remarkably attenuates APAP-induced hepatotoxicity, as repair liver damage and improve survival. Moreover, Ginsenoside Rc treatment also modulates genes involved in APAP metabolism, leading to the decrease of NAPQI and resulting in the alleviation of fatal oxidative stress and inflammatory response after APAP exposure, along with the expression of their related indicators. Furthermore, our RNA-seq and molecular docking analysis implied effective stimulatory effects of FXR expression and FXR transcriptional activity after Ginsenoside Rc treatment. Of note, due to the lack of FXR in mice and MPHs, ginsenoside Rc can no longer play the original protective role against hepatotoxicity and cell damage caused by APAP, and it is difficult to improve the corresponding survival rate, hepatic apoptosis, NAPQI generation, fatal oxidative stress, and the inflammatory response induced by APAP, and the expression of related genes. In summary, our results indicated that Ginsenoside Rc could act as an effective FXR activator and can effectively regulate FXR-induced antioxidant stress and eliminate inflammation, and anti-apoptotic function.